A Self‐Assembled Oligopeptide as a Versatile NMR Alignment Medium for the Measurement of Residual Dipolar Couplings in Methanol. (13th September 2017) - Lei, Xinxiang; Qiu, Feng; Sun, Han; Bai, Liwen; Wang, Wen‐Xuan; Xiang, Wensheng; Xiao, Hongping
Abstract: Residual dipolar coupling (RDC) is a powerful structural parameter for the determination of the constitution, conformation, and configuration of organic molecules. Herein, we report the first liquid crystal‐based orienting medium that is compatible with MeOH, thus enabling RDC acquisitions of a wide range of intermediate to polar organic molecules. The liquid crystals were produced from self‐assembled oligopeptide nanotubes (AAKLVFF), which are stable at very low concentrations. The presented alignment medium is highly homogeneous, and the size of RDCs can be scaled with the concentration of the peptide. To assess the accuracy of the RDC measurement by employing this new medium, seven bioactive natural products from different classes were chosen and analyzed. The straightforward preparation of the anisotropic alignment sample will offer a versatile and robust protocol for the routine RDC measurement of natural products.